2020
DOI: 10.1093/alcalc/agaa124
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Stressors Predicting Increased Drinking During the COVID-19 Crisis: A Longitudinal National Survey Study of Workers in Finland

Abstract: Aims The global crisis caused by the outbreak of a novel coronavirus rapidly increased working remotely in many countries. The aim of this study was to analyze psychological stressors predicting increased drinking during the COVID-19 crisis. Also, individual and socio-demographic differences were analyzed. Methods A nationally representative sample of Finnish workers (N = 1308) was collected before the crisis in September–Oct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
1
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(58 citation statements)
references
References 64 publications
1
43
1
3
Order By: Relevance
“…Twenty of these papers included a single question such as, “Since the start of the pandemic, has your alcohol use increased, decreased, or stayed the same?” In general, most papers ( n = 24) reported both increased and decreased alcohol use among different segments of the population. An equal number of papers ( n = 11) reported that more people increased their drinking ( Bartoszek et al, 2020 , Every-Palmer et al, 2020 , Górnicka et al, 2020 , Grossman et al, 2020 , Huckle et al, 2020 , Rolland et al, 2020 , Stanton et al, 2020 , Tran et al, 2020 , Vanderbruggen et al, 2020 , Weerakoon et al, 2020 , Zajacova et al, 2020 ), and decreased their drinking during the pandemic at the population level ( Alpers et al, 2021 , Chodkiewicz et al, 2020 , Constant et al, 2020 , Dozois, 2021 , Koopmann et al, 2020 , Kriaucioniene et al, 2020 , Oksanen et al, 2021 , Rodriguez et al, 2020 , Scarmozzino and Visioli, 2020 , Sidor and Rzymski, 2020 , Szajnoga et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Twenty of these papers included a single question such as, “Since the start of the pandemic, has your alcohol use increased, decreased, or stayed the same?” In general, most papers ( n = 24) reported both increased and decreased alcohol use among different segments of the population. An equal number of papers ( n = 11) reported that more people increased their drinking ( Bartoszek et al, 2020 , Every-Palmer et al, 2020 , Górnicka et al, 2020 , Grossman et al, 2020 , Huckle et al, 2020 , Rolland et al, 2020 , Stanton et al, 2020 , Tran et al, 2020 , Vanderbruggen et al, 2020 , Weerakoon et al, 2020 , Zajacova et al, 2020 ), and decreased their drinking during the pandemic at the population level ( Alpers et al, 2021 , Chodkiewicz et al, 2020 , Constant et al, 2020 , Dozois, 2021 , Koopmann et al, 2020 , Kriaucioniene et al, 2020 , Oksanen et al, 2021 , Rodriguez et al, 2020 , Scarmozzino and Visioli, 2020 , Sidor and Rzymski, 2020 , Szajnoga et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…Twenty studies reported a change in frequency, amount, or severity of alcohol use during the COVID-19 pandemic compared to pre-pandemic use ( Alpers et al, 2021 , Ammar et al, 2020 , Barbosa et al, 2021 , Błaszczyk-Bębenek et al, 2020 , Boschuetz et al, 2020 , Callinan et al, 2021 , Callinan et al, 2021 , Đogaš et al, 2020 , Huckle et al, 2020 , Jackson et al, 2021 , Newby et al, 2020 , Niedzwiedz et al, 2021 , Oksanen et al, 2021 , Rolland et al, 2020 , Sallie et al, 2020 , Vanderbruggen et al, 2020 , Villanueva et al, 2021 , Wardell et al, 2020 , Weerakoon et al, 2020 , Winkler et al, 2020 ), two studies compared alcohol use at two or more time points during the pandemic ( Killgore et al, 2021 , Pollard et al, 2020 ), and one study compared the severity of alcohol use in Hubei province, the epicenter of COVID-19, compared with respondents from other provinces in China ( Ahmed et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…A summary of studies from different countries (China, Finland, Belgium, Chile, US, Poland) reports increased alcohol consumption during lockdown compared to prelockdown [ 22 , 24 , 26 30 ]. Specifically, many studies report an increase in binge drinking, as well as solitary drinking [ 27 , 29 , 31 , 32 ▪ , 33 , 34 ]. Although some studies observed an increase in drinking among women [ 27 , 35 ], others did not observe gender differences in alcohol use patterns [ 36 ].…”
Section: Text Reviewmentioning
confidence: 99%
“…A summary of factors associated with increased alcohol use include psychological distress related to COVID-19 [ 32 ▪ , 33 , 35 , 39 ], increased availability of free time [ 40 ], misinformation about alcohol, heavy drinking prepandemic, job loss, eating more, changes in sleep, higher anxiety and depression [ 41 44 ], living with children [ 45 ], reduced physical activity [ 46 ], loneliness, [ 47 ], cyberbullying, victimisation at work [ 33 ], lower social connectedness and having one child under the age of 18 years [ 48 ]. In a US-based online survey, increase in alcohol-related problems was independent of the amount of alcohol consumption [ 29 ].…”
Section: Text Reviewmentioning
confidence: 99%
“…Bemerkenswert war dabei, dass die Erhöhung vorwiegend bei Personen mit einem schon bestehenden Binge-Drinking Verhalten beobachtet wurde [145]. Weitere Studien fanden eine Zunahme des Alkoholkonsums zwischen 17 und 29 %, wobei verschiedene Formen psychischer Belastungen jeweils deutlich mit einer Zunahme des Alkoholkonsum assoziiert waren [146,147]. Besonders deutlich zeigte sich das in einer US-amerikanischen Untersuchung, in der die stärksten Zunahmen des Konsums bei Personen mit komorbider Depression (41 % Steigerung) und Angststörungen (59 % Steigerung) zu finden waren [148].…”
Section: Substanz-bezogene Störungenunclassified